A (re)construção do trabalho do professor de inglês pela linguagem - Tognato, Maria Izabel Rodrigues (2009)
This thesis aimed to contribute to the understanding of English Language teacher s work from Elementary and High School, from Public School, in the interior of Paraná State, in Brazil, through the analysis and interpretation of (re)configurations constructed on educational acting in texts produced by teachers from the state school, about this situation of work. This way, we intend to show how the educational work is (re)configured by its protagonists in texts produced by themselves about their professional activity. To develop this study, we adopt theoretical-methodical presuppositions of the sociodiscursive interactionism (ISD) (BRONCKART, 1999/2003/2007, 2004, 2006, 2008), an interdisciplinary area from Psychology, which attributes a fundamental role in the human development to the acting and the language. Considering the work as a way of acting and a factor which leads to the development and, more specifically, considering the educational work, which is institutionally regulated and that has as an intention to form the citizen, we propose to understand the connections between the language, a constitutive aspect of the human being, and the work, a central point for the understanding of the current society. This research investigates, more specifically, the connections between language and the teacher s work considering the different levels through which this work is constituted. We also assume theoretical aspects from the Sciences of the Work as the Ergonomics of the Activity (AMIGUES, 2004; SAUJAT, 2002, 2004) e, more necessarily, the Clinic of the Activity, based on the Psychology of Work (CLOT, 1999/2006; FAÏTA, 2002, 2004, 2005). This inquiry was carried through the procedure of data collection of the instruction to the double, following the perspective of the Psychology of the Work, Clinic of the Activity and Ergonomics of the Activity, taking as a basis the studies developed by Oddone et al. (1981). This procedure could allow the teacher to search for elements that supply subsidies for a critical analysis of theoretical-methodical presuppositions present at his speech, helping him to perform with a greater scientific ability on educational acting seen as work. The speeches of the investigated teachers had been analyzed according to the methodological procedures of the sociodiscursive interactionism (BRONCKART, 1999/2003/2007, 2004, 2006, 2008), considering the vision of education as a work , inspired by the Ergonomics of the Activity and the Clinic of the Activity for the interpretation of the results. We present, in this research, a synthesis of the pressupositions we assume and some questions such as: a) the work; b) educational work; c) work of English Language teacher; considering its connections in the society contemporary and with the language, beyond the c) questions about the procedure of data collection and analysis as well. Finally, we conclude the texts produced through the procedure of the instructions to the double, by the worker, can offer rich subsidies for the understanding of his situation of work. In the case of the educational work, we can not only understand what the professor carries through as what prevents his professional practice (CLOT, 1999/2006). Thus, understanding the constitutive and representative aspects of this work in a better way, it is possible to be more prepared to know how to deal with the conflicts and the choices in search for alternative solutions